2017
DOI: 10.1002/jcb.26469
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: Effect of microRNA‐128 on cisplatin resistance of glioma SHG‐44 cells by targeting JAG1

Abstract: This current study intends to investigate the effect of microRNA-128 (miR-128) on cisplatin (DDP) resistance in glioma SHG-44 cells. SHG-44/DDP cells were transfected with miR-128 antisense oligonucleotide (ASO) and assigned into blank, resistance, NC, anti-miR-128, miR-128 mimic, si-JAG1, and anti-miR-128 + si-JAG1 groups. qRT-PCR and Western blotting were employed for determining expression of miR-128, JAG1, Bax and Bcl-2. MTT assay, Giemsa staining, and flow cytometry were applied to detect DDP resistance, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 38 publications
2
8
0
Order By: Relevance
“…Moreover, upregulation of JAG1 oncogene is observed in nilotinib and imatinib-resistant myeloblastic leukemia cells 29. miR-26b and miR-128 contribute to the resistance of nasopharyngeal carcinoma or glioma to cisplatin by downregulating JAG1 30,31. Consistent with previous studies, we observed that knockdown of JAG1 enhanced the chemosensitivity of DTX-tolerated PC cells to DTX, and the biological function of JAG1 was rescued by miR-34a-5p inhibitor.…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, upregulation of JAG1 oncogene is observed in nilotinib and imatinib-resistant myeloblastic leukemia cells 29. miR-26b and miR-128 contribute to the resistance of nasopharyngeal carcinoma or glioma to cisplatin by downregulating JAG1 30,31. Consistent with previous studies, we observed that knockdown of JAG1 enhanced the chemosensitivity of DTX-tolerated PC cells to DTX, and the biological function of JAG1 was rescued by miR-34a-5p inhibitor.…”
Section: Discussionsupporting
confidence: 89%
“…In cells transfected with pre-miR-128 and pRL-JAG1-WT, luciferase activity significantly decreased relative to that in cells cotransfected with the control precursor or mutated versions of the target (Figure 2D). These results demonstrate that miR-128 directly suppresses the expression of JAG1 through targeting seed sequences in the 3 -UTR of JAG1, in agreement with a previous report (Yi et al, 2018). To test the role of JAG1 in neurogenic differentiation, a small interfering RNA (siRNA) of JAG1 was designed, synthesized, and verified (Figure 2E).…”
Section: Notch Pathway Activation and Roles In The Expression Of Neursupporting
confidence: 89%
“…However, resistance to chemotherapy occurs inside cancer cells, reducing treatment efficiency, and platinum-based chemotherapy is no exception [ 110 ]. Overcoming drug resistance by revealing the molecular mechanisms that mediate cisplatin resistance will have important clinical value in improving the treatment outcome of brain tumors [ 111 , 112 ]. Many research have been conducted on the mechanism of cisplatin resistance acquisition in brain tumor cells.…”
Section: Resistance Mechanism Of Platinum-based Anticancer Drugs In Brain Tumorsmentioning
confidence: 99%